Simple Financial Statements Training for Business Actors in West Java Indonesia - Riwayati, Hedwigis Esti; Mawardi, Rizal; Sorongan, Fangky Antoneus; Amelia, Tifa Noer; Zainon, Saunah; Misman, Faridah Najuna (Dinasti International Journal of Management Science, 2024)
This training aims to improve the understanding and skills of Ikanesia West Java business actors in recording financial transactions systematically and accurately. This activity is a form of community service collaboration between Perbanas Institute and Universiti Teknologi Mara Malaysia. In this training, participants are given a basic understanding of accounting, the benefits of financial record-keeping, as well as simple record-keeping techniques that can be applied in the fisheries business. With this training, it is hoped that business actors can increase transparency and efficiency in their financial management.